Does nitrate suppress phosphorus release from sediment? A case study in Lake Kasumigaura, Japan - Ryuichiro Shinohara; Kenji Tsuchiya; Ayato Kohzu (Journal of Hydrology: Regional Studies)
Study Region: Lake Kasumigaura, a shallow, hypereutrophic lake in Japan. Study focus: Because nitrate (NO3–) is an oxidant, it suppresses the release of PO43- from bottom sediments through its role in the oxidation/reduction reactions of Fe. We investigated whether NO3- can suppress the release of PO43- at Lake Kasumigaura. New hydrological insights for the region: Sediment analyses revealed no significant correlation between porewater NO3– concentrations and either PO43– concentrations or the fluxes of PO43– from the sediments. Furthermore, the porewater NO3– concentration was approximately 0 mg N L–1 at depths below the sediment surface. We further observed that the relationship between oxidation-reduction potential (ORP) and Fe concentrations exhibited U-shaped characteristics. The oxidation and reduction reactions of Fe appeared to occur at depths below 10 cm, significantly deeper than the layers where PO43⁻ release takes place. The negligible concentration of NO3– in the sediment porewater, as well as the relationship between Fe and P species, appears to reflect that NO3- did not suppress PO43- release from sediment at Lake Kasumigaura.